2017
DOI: 10.1134/s1063779616060022
|View full text |Cite
|
Sign up to set email alerts
|

The study of the thermal neutron flux in the deep underground laboratory DULB-4900

Abstract: We report on the study of thermal neutron flux using monitors based on mixture of ZnS(Ag) and LiF enriched with a lithium-6 isotope at the deep underground laboratory DULB-4900 at the Baksan Neutrino Observatory. An annual modulation of thermal neutron flux in DULB-4900 is observed. Experimental evidences were obtained of correlation between the long-term thermal neutron flux variations and the absolute humidity of the air in laboratory. The amplitude of the modulation exceed 5% of total neutron flux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…At Baksan Neutrino Observatory (Russia) neutron flux was studied by using a liquid scintillator detector combined with 3 He proportional counters uniformly distributed within the scintillator volume [6]. In addition, the thermal neutron flux was measured recently at the Baksan Neutrino Observatory [7] by using a scintillator detector based on 6 LiF:ZnS(Ag) components. The 3 He proportional counters were used at Canfranc Underground Laboratory (Spain) [8], Kamioka neutrino observatory (Japan) [9], and YangYang underground laboratory (South Korea) [10].…”
Section: Introductionmentioning
confidence: 99%
“…At Baksan Neutrino Observatory (Russia) neutron flux was studied by using a liquid scintillator detector combined with 3 He proportional counters uniformly distributed within the scintillator volume [6]. In addition, the thermal neutron flux was measured recently at the Baksan Neutrino Observatory [7] by using a scintillator detector based on 6 LiF:ZnS(Ag) components. The 3 He proportional counters were used at Canfranc Underground Laboratory (Spain) [8], Kamioka neutrino observatory (Japan) [9], and YangYang underground laboratory (South Korea) [10].…”
Section: Introductionmentioning
confidence: 99%
“…At DULB-4900 (4900 m.w.e.) the same authors observed a seasonal variation in the absolute air humidity with maximum in summer and a correlated variation of ≈ 5% in the thermal neutron rate [21]. The increase of the thermal rate with the humidity was attributed to a better moderation of the neutrons both in the humid air and when exiting from a humid rock as well as higher albedo of the neutrons incoming into the rock.…”
Section: Long-term Evolution Of the Environmental Datamentioning
confidence: 82%
“…A limited number of studies show the time evolution of the thermal neutron rate in UG laboratories, employing 6 LiF+ZnS(Ag) scintillators with sensitivity to the thermal range [15,20,21]. The present study is, to our knowledge, the first long-term measurement carried out with a spectrometer composed of moderated 3 He counters with sensitivity over a wide range of neutron energies.…”
Section: Introductionmentioning
confidence: 88%
“…A limited number of studies show the time evolution of the thermal neutron rate in UG laboratories, employing 6 LiF+ZnS(Ag) scintillators with sensitivity to the thermal range [15,20,21]. The present study is, to our knowledge, the first long-term measurement carried out with a spectrometer composed of moderated 3 He counters with sensitivity over a wide range of neutron energies.…”
Section: Introductionmentioning
confidence: 89%